On characterization of cohesive zone model (CZM) based upon digital image correlation (DIC) method. (1st February 2022) - Huo, Xintao; Luo, Quantian; Li, Qing; Zheng, Gang; Sun, Guangyong
Highlights: A new method to extract the traction-separation law based on DIC technique. Analytical model of mode I fracture bridging the TSL and the global response. Determination of CZM without priori shape of the traction-separation law. Accurate FE modeling with non-linear damage determined by DIC. Abstract: Cohesive zone model (CZM) has been extensively applied in numerical simulation of interfacial fracture behaviors such as composite delamination and fracture of adhesive joints. Accurate and efficient identification of CZM parameters signifies an important research topic to enable reliable analysis and design of these structures. This paper aims to derive the actual traction-separation law of CZM by means of experimental measurement with only digital image correlation (DIC) technique. A double cantilever beam (DCB) specimen was employed for experimental tests and a semi-empirical analytical model was developed to associate the traction-separation law with the global loading response. Explicit formulae of the initial stiffness, maximum traction stress and damage evolution were derived. In this study, the DCB specimens bonded with a ductile adhesive layer of Araldite® 2015 were fabricated and experimentally tested. The displacement distribution of the adhesive layer was quantified as the fundamental data for identification of CZM parameters. The initial stiffness, maximum traction stress and damage evolution of CZM were identified accurately. Based upon the extracted CZM parameters in the present work, a finite element (FE) model was developed and verified with the experimental results. Furthermore, a FE model with a traditional linear damage evolution was also established for comparison, thereby demonstrating the effectiveness of the proposed method for extracting the traction-separation law of CZM. By employing the present approach, the real traction-separation law can be better presented and accurate simulation of adhesive joint can be achieved. Graphical abstract: Image, graphical abstract